2004
DOI: 10.1207/s15324796abm2702_7
|View full text |Cite
|
Sign up to set email alerts
|

Risk perceptions and their relation to risk behavior

Abstract: The behavior motivation hypothesis was supported in this longitudinal study, but the opposite conclusion (i.e., that higher risk led to less protective behavior) would have been drawn from an incorrect test based only on cross-sectional data. Health researchers should take care in formulating and testing risk-perception-behavior hypotheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
611
4
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 692 publications
(686 citation statements)
references
References 9 publications
32
611
4
14
Order By: Relevance
“…Media coverage of health-related events has become so important that several surveillance systems now rely on active trolling of internet news media to detect emerging disease threats [7,8]. It is a relatively inexpensive way of exposing the population to information regarding their health [2] and has the potential to reach a large proportion of the population, particularly groups that may be difficult to access through more traditional approaches [5,9,[9][10][11]. For instance, mass media campaigns based on communication for behavioral impact and social change have been shown to be an effective intervention for smoking cessation in adults [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Media coverage of health-related events has become so important that several surveillance systems now rely on active trolling of internet news media to detect emerging disease threats [7,8]. It is a relatively inexpensive way of exposing the population to information regarding their health [2] and has the potential to reach a large proportion of the population, particularly groups that may be difficult to access through more traditional approaches [5,9,[9][10][11]. For instance, mass media campaigns based on communication for behavioral impact and social change have been shown to be an effective intervention for smoking cessation in adults [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Questions related to MRSA national rate (18%) and risk factors for acquisition (46%) obtained less correct answers as was also observed by Easton et al 9 The perceived risk was influenced by the use of protective and containment measures. Existing prevention measures increased individual situation control perception and reduced risk perception as described by Brewer et al 10 Patient intrinsic risk factors were identified, and patient risk was well perceived by most of the respondents and interviewees.…”
Section: Discussionmentioning
confidence: 79%
“…Hivert, Warner, Shrader, Grant, and Meigs (2009) examined previous behavioural efforts and future intentions among at-risk groups with a high and low risk perception, and found no difference between the groups. However, risk perception, in conjunction with positive outcome expectations, is regarded as a prerequisite for adopting protective behaviour (Brewer, Weinstein, & Cuite, 2004;Janz & Becker, 1984;Leventhal, Leventhal, & Cameron, 2001;Schwarzer, 2008;Rogers, 1975). Since type 2 diabetes is highly preventable by lifestyle changes, a correct perception of risk and its relation to behaviour is vitally important (Critchley, Hardie, & Moore, 2012;Grant et al, 2013).…”
Section: *Statement Of Contributionmentioning
confidence: 99%